Can Light Contact with the Police Motivate Political Participation? Evidence from Traffic Stops. (22nd November 2022) - Christiani, Leah; Shoub, Kelsey
Abstract: Harsh, highly intrusive, personal contact with the criminal justice system has been shown to politically demobilize, but it is unclear whether less intrusive forms of police contact have any political effects. As the modal type of involuntary police–citizen contact is less invasive and more routine (e.g., a traffic stop), it is critical to understand the ramifications of lighter forms of contact. We argue that, unlike harsh police contact, light, personal, police contact can mobilize individuals, under certain circumstances. When a negative encounter with the police—even if it is minor—runs counter to prior expectations, people experiencing the contact are mobilized to take political action. Using 3 years of observational data and an original survey experiment, we demonstrate that individuals who receive tickets or are stopped by the police are more likely to participate in politics. These effects are most pronounced for individuals with positive evaluations of the police, often White respondents.